Impact of Stress on the Employee Performance: A Case of Pharmaceutical Industry of KPK - FARAH SALEEM; MUHAMMAD IRFAN; DR. AMIR ISHAQUE (Journal of Business & Tourism, 2021)
Every individual experiences stress whether it may be in family, business, study, any work, or any other social and economic activities. In organizations employees feel stress which hinder their job performance. The factors that cause stress in employees at their work place are called as job stressors. There are two dimensions of stressors; one is challenge stressors and second is hindrance stressors. Employees working in these organizations need to be very attentive and efficient because the products are directly related with human health. Any carelessness or defect in these products can take someone’s life. This makes it important to study the level of stress among the employees working in pharmaceutical industry and its impact on their performance. Overall purpose of the study was to find the impact of challenge and hindrance stressors on employee performance. Using simple random sampling technique, data was taken from 213 employees of three well known pharmaceutical companies of Peshawar KPK. Using simple linear regression analysis, it was found that role overload, role ambiguity and role conflict has negative affect on employee performance while level of responsibility has positive impact on overall employee performance.